Jumping Translocations of 1q in Myelodysplastic Syndrome and Acute Myeloid Leukemia: Report of Three Cases and Review of Literature - T. Couture; K. Amato; A. DiAdamo; P. Li (Case Reports in Genetics)
Jumping translocations of 1q refer to the break-off of chromosome 1q as a donor fusing to two or more recipient chromosomes. We detected jumping translocations of 1q in three patients with initial diagnosis of myelodysplastic syndrome (MDS) and later progression to acute myeloid leukemia (AML). Review of literature found jumping translocations of 1q in 30 reported cases of MDS and AML. The cytogenetic findings from these 33 cases showed that seven cases had a stemline clone and 26 cases had de novo jumping translocations of 1q in which 5% of cell lineages had additional structural rearrangements. In 75% of cases, the 1q donor jumped to the short arm of recipient acrocentric chromosomes. Approximately 82% of the fusions occurred in the telomeric regions of short and long arms and 18% occurred in the pericentric or interstitial regions of recipient chromosomes. Hypomethylation of the donor 1q pericentromeric region and shortened telomeres in recipient chromosomes were associated with the formation of jumping translocations. Jumping translocations of 1q as an indication of chromosomal instability pose high risk for progression of MDS to AML and a poor prognosis. Further understanding of underlying genomic defects and their clinical significance will improve overall treatment and patient care.